Pengaruh Net Profit Margin (NPM), Inflasi, Dan Return On Asset (ROA) Terhadap Harga Saham (Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2023) - Rizantha, Pranada Elvan; Lestari, Wuryaningsih Dwi (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
Capital markets play a crucial role in driving economic growth in various countries, both developed and developing. Through the capital market, a company will obtain a fund to carry out its activities. This study aims to analyze the effect of Net Profit Margin (NPM), inflation, and Return on Asset (ROA) on stock prices in banking sub-sector companies listed on the Indonesia Stock Exchange for the period 2020-2023. The research method used is quantitative with an associative approach. The sampling technique was carried out using purposive sampling with a total sample size of 41 companies. Data analysis using multiple linear regression with classical assumption tests. The results showed that partially, while Inflation and Return on Assets (ROA) significantly influence stock prices. Simultaneously, all three independent variables significantly influence stock prices. Data analysis was conducted using multiple linear regression with classical assumption tests. The results of the study indicate that, partially, Net Profit Margin (NPM) does not significantly influence stock prices, while Inflation and Return on Assets (ROA) significantly influence stock prices. Simultaneously, all three independent variables significantly influence stock prices